Innovative educational congklak media in prasiaga scout activities: stimulating critical thinking and social skills in early childhood - Nuraisyah; Kurnia, Rika; Herman; Herlina; Bactiar, Yusri; Hajerah (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
Critical thinking skills are essential competencies that need to be developed from an early age, as they play a vital role in the processes of analysis, problem-solving, and decision-making. Study aimed to develop and examine the effectiveness of the innovative traditional game "Congkalak Edukatif" in stimulating critical thinking and social skills among 5–6-year-old children during Prasiaga Scout activities at TK IT Asshiddiq. The research method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were children aged 5–6 years participating in Prasiaga Scout activities. The results indicated that the implementation of the Congkalak Edukatif game significantly enhanced children's critical thinking abilities, as evidenced by the increased posttest scores compared to the pretest in the aspects of analysis, problem-solving, and decision-making. Furthermore, this game was also effective in developing children's social skills, such as communication skills, cooperation, sportsmanship, and emotional regulation in social interactions. The enjoyable, socially interactive play experience provided by the Congkalak Edukatif game encouraged children to learn teamwork, understand rules, and build empathy towards their peers. Thus, Congkalak Edukatif can serve as an innovative and effective learning media alternative for improving critical thinking and social skills in early childhood, particularly within Prasiaga Scout activities. This article makes a significant contribution to the development of future science by introducing Congklak media as an innovative media that has been proven to be effective in stimulating critical thinking skills and social skills in early childhood, thus opening a new paradigm in learning practices that integrate aspects of analysis, problem solving, decision making, and social interaction from preschool age.